2019
DOI: 10.17576/jkmjc-2019-3502-22
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectories of Creative Content Protecting Law in Indonesia: Dealing with the Challenge and Advancing the Potential

Abstract: The article aims at determining the legal protection of creative content uploaded by the creators through online media as well as the challenges faced by the creators in protecting their works. This research includes descriptive normative of the legal research that describes the legal protection and the challenges faced by the creators in protecting their works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Related to several studies regarding Islamic banking spin-offs including Yuspin and Wardiono (2017) concluded that the spin-off provisions were sufficient to meet the requirements obtained for the development of Islamic banks in the future and the time limit was to provide sufficient time to prepare the spin-off. And initiate a comprehensive business plan for the Separation.…”
Section: Previous Study-spin Offmentioning
confidence: 99%
“…Related to several studies regarding Islamic banking spin-offs including Yuspin and Wardiono (2017) concluded that the spin-off provisions were sufficient to meet the requirements obtained for the development of Islamic banks in the future and the time limit was to provide sufficient time to prepare the spin-off. And initiate a comprehensive business plan for the Separation.…”
Section: Previous Study-spin Offmentioning
confidence: 99%
“…Thirdly, the ijarah contract is formed when the munqtaridh gives money for the transaction, and the money is subject to a membership charge and an ijarah fee. Finally, there is kafalah, in which munqtaridh acts as a guarantor between the debtor and the merchant for the debtor's responsibilities originating from transactions with the sharia card, as a result of the act of 'guaranteed wages' (Yuspin & Wardiono, 2017), where the conditions of this contract are likewise contained in the fatwa's third paragraph.…”
Section: Introductionmentioning
confidence: 99%